Uso do efluente da suinocultura em bananeira ‘Terra’ - Spadeto, Marjorie de Freitas (2020)
The swine culture is an important economic activity in the national scenario, however this line of agriculture is responsible for considerable waste volumes that can cause negative impacts when dumped in an inappropriate manner to the environment. In turn